2014
DOI: 10.1007/s10461-014-0847-3
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Cannabis Use and Adherence to Antiretroviral Therapy Among People Who Use Illicit Drugs in a Canadian Setting

Abstract: Background Cannabis is increasingly prescribed clinically and utilized by people living with HIV/AIDS (PLWHA) to address symptoms of HIV disease and to manage side effects of antiretroviral therapy (ART). In light of concerns about the possibly deleterious effect of psychoactive drug use on adherence to ART, we sought to determine the relationship between high-intensity cannabis use and adherence to ART among a community-recruited cohort of HIV-positive illicit drug users. Methods We used data from the ACCES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 50 publications
2
31
1
1
Order By: Relevance
“…They found that persons with cannabis dependence were less adherent both by pill count and self-report; however, differences in self-reported adherence were no longer observed when analyses were controlled for age, education and alcohol consumption. Consistent with our results, a recent longitudinal cohort study of illicit drug users with HIV in Vancouver found no association between daily marijuana use and treatment adherence in multivariable analysis [16]. Similarly, in a recent analysis of a Florida cohort of PWH, no relationship between marijuana use and HIV outcomes was observed [10].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They found that persons with cannabis dependence were less adherent both by pill count and self-report; however, differences in self-reported adherence were no longer observed when analyses were controlled for age, education and alcohol consumption. Consistent with our results, a recent longitudinal cohort study of illicit drug users with HIV in Vancouver found no association between daily marijuana use and treatment adherence in multivariable analysis [16]. Similarly, in a recent analysis of a Florida cohort of PWH, no relationship between marijuana use and HIV outcomes was observed [10].…”
Section: Discussionsupporting
confidence: 90%
“…having marijuana dependence/marijuana use disorder (MUD)) [15] are associated with worse ART adherence. In contrast, a recent study of illicit drug users with HIV found no association between daily marijuana use and optimal treatment adherence [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Marijuana use is frequent in PLWHA, both recreationally and therapeutically (SAMHSA 2004) in its synthetic form (Δ 9 -THC; MARINOL ® (dronabinol) (ElSohly et al 2001). In contrast to the consistent reports of non-adherence to ART by alcohol-using PLWHA, high-frequency cannabis use has not been reported to interfere with adherence to ART (Slawson et al 2014). This is an important contrast in behavioral consequences of the use of these two most frequently abused substances that is likely to have an impact on the overall biomedical consequences and comorbidities in PLWHA.…”
Section: Introductionmentioning
confidence: 91%
“…Alcohol and illicit drug use are significant predictors of non-adherence to ART (Bell et al 1998; Bing et al 2001; Khalsa and Royal 2004; Lee et al 2001; Nair et al 2004). PLWHA with alcohol and drug use disorders are consistently found to be non-adherent to ART and have a higher likelihood of virologic non-suppression and adverse disease outcomes (Ghosn et al 2014; Kino and Chrousos 2003; Slawson et al 2014). While cannabis use has not been linked to decreased ART adherence (Slawson et al 2014), both alcohol and cannabis use in PLWHA are associated with high-risk sexual behaviors (Hendershot et al 2007; Raj et al 2009; Shuper et al 2009), increased vaginal (Theall et al 2008) and seminal viral shedding (Ghosn et al 2014), and heightened risk of HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies across studies may be a result of variations in the relationship between cannabis use and ART adherence, both related to the above-described differences in cannabis use frequency/dependence categorizations as well as differences in the overall sample populations and confounding variables taken into account. Previously, using data from the ACCESS cohort we demonstrated that high-intensity cannabis use was not associated with a greater or lesser likelihood of optimal ART adherence (Slawson et al, 2014). While similar findings have been recorded in studies of more general HIV-positive samples (i.e., inclusive of both drug-using and non drug-using individuals) (Rosen et al, 2013), others have concluded adherence rates are significantly lower among cannabis users (Tucker et al, 2003; Wilson et al, 2004).…”
Section: Discussionmentioning
confidence: 96%